All Clear for Takeoff: Evidence from Airports on the Effects of Infrastructure Privatization - Howell, Sabrina T; Jang, Yeejin; Kim, Hyeik; Weisbach, Michael S (Review of Financial Studies, 2026)
Abstract We study privatization and corporate ownership in transportation infrastructure, focusing on global airports. Privatization in general does not improve performance. However, private equity (PE) ownership has strong and persistent positive effects on efficiency, volume, and quality, with positive externalities for the local economy. We address selection using close auctions where PE and non-PE firms bid. PE funds expand physical capacity and encourage larger planes while adding low-cost carriers and international routes. They are especially effective in countries with more corruption or state-owned flag carriers. In contrast, the poorer performance of non-PE acquirers may reflect private benefits and historical state ties.